2005
DOI: 10.1002/path.1715
|View full text |Cite
|
Sign up to set email alerts
|

MALT lymphoma with t(14;18)(q32;q21)/IGH‐MALT1 is characterized by strong cytoplasmic MALT1 and BCL10 expression

Abstract: Mucosa-associated lymphoid tissue (MALT) lymphoma is specifically associated with t(11;18)(q21;q21), t(1;14)(p22;q32) and t(14;18)(q32;q21). t(11;18)(q21;q21) fuses the N-terminus of the API2 gene to the C-terminus of the MALT1 gene and generates a functional API2-MALT1 product. t(1;14)(p22;q32) and t(14;18)(q32;q21) bring the BCL10 and MALT1 genes respectively to the IGH locus and deregulate their expression. The oncogenic activity of the three chromosomal translocations is linked by the physiological role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 35 publications
7
102
2
5
Order By: Relevance
“…7,[27][28][29][30] In MALT lymphoma, deregulation of the expression of MALT1 gene due to chromosomal translocations t(11;18)(q21; q21) and t(14;18)(q32;q21) seems to be one of the main pathogenic mechanisms leading to reduced apoptotic activity. 12,15,22,[31][32][33] In contrast to what has been described in gastric MALT lymphomas, our results did not indicate the presence of t (11;18). This translocation has been extensively examined in gastric MALT lymphomas and is associated with cases of a more advanced stage or those lacking responses to Helicobacter pylori eradication.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…7,[27][28][29][30] In MALT lymphoma, deregulation of the expression of MALT1 gene due to chromosomal translocations t(11;18)(q21; q21) and t(14;18)(q32;q21) seems to be one of the main pathogenic mechanisms leading to reduced apoptotic activity. 12,15,22,[31][32][33] In contrast to what has been described in gastric MALT lymphomas, our results did not indicate the presence of t (11;18). This translocation has been extensively examined in gastric MALT lymphomas and is associated with cases of a more advanced stage or those lacking responses to Helicobacter pylori eradication.…”
Section: Discussioncontrasting
confidence: 99%
“…12,15,[31][32][33]35 The nuclear expression of bcl10 has been proposed as a surrogate of NF-kB activation after (11;18)(q21;q21), t(1;14)(p22;q32), while strong cytoplasmic expression has been linked with t(14;18)(q32;q21). 7,12,22,35,36 Strikingly, our data show a clear association between nuclear bcl10, increased expression of p-IkBa, and shorter time to failure. This, in addition to providing predictor parameters, suggests tentative therapeutic targets.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…12 We did not find any structural aberrations in the thyroid lymphomas in our series. Other studies have confirmed the absence of t(14;18)(q32;q21) in thyroid lymphomas, 13,16,27,41 however, t(11;18) and t(3;14) have been reported in extranodal marginal zone lymphoma of the thyroid. 14,26,32,38 Several studies have confirmed differences in prevalence of extranodal marginal zone lymphoma-associated translocations at various anatomic sites and suggest that distinct molecular pathways are involved in the pathogenesis of extranodal marginal zone lymphoma.…”
Section: Discussionmentioning
confidence: 81%